A Model of Amateur Boxer Development to be Thailand National Amateur Boxing Athletes - Boonthom, Riman (Academic Journal of Thailand National Sports University, 2022)
The purposes of this research were to 1) study factors of developing amateur boxers to Thailand boxing athletes, 2) establishing a model enhancing amateur to achieve their goals, 3) verifying effectiveness of the model. Two hundred and twenty four samples participated in the study. They were qualified persons and amateur boxing experts included academicians, sport association administrators referees, coaches, amateur boxing athletes, correspondents, and sponsors. Interviews and questionnaires were used to collect data which were analyzed by mean of factor analysis and discriminant analysis. The results were as follows: 1) a model for amateur boxer development to Thailand amateur boxing athletes was composed of the amateur boxing athlete selection, the athlete's potential development, the provision of competition opportunities for athletes, the provision of support and the administrative measures. 2) A model of amateur boxer development to Thailand amateur boxing athletes consisted of conceptual idea, principles, objectives, and developing operations in the five stated factors, conditions and model limitations. 3) In verifying the model accuracy in the real situation, this model could be applicable in predicting the Thai national amateur boxing athletes from general boxers. The result of discriminant analysis of the model was 87% as the result this model could be effectively applicable. The recommendations of the research are as follows: 1) In applying the Model of Amateur Boxer Development to Thailand National Amateur Boxing Athletes, related persons to amateur boxer development should have a clear understanding of each element in order to implement the model efficiently and be able to achieve the goals of the development of amateur boxers. 2) Staff and related persons who are in charge of the amateur boxer development should have had knowledge expertise and ability to manage the model professionally effectively and acceptingly at the national level.